Additive Functions and Chain Complexes of Projective Modules - Sharko, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We study additive functions given on a category of finitely generated projective modules. Using these functions, we define p-minimal epimorphisms and give a necessary and sufficient condition for their existence. We prove results concerning the structure of p-minimal chains of projective modules.